2014
DOI: 10.1016/j.eats.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

“Relaxed” Biceps Proximal Tenodesis: An Arthroscopic Technique With Decreased Residual Tendon Tension

Abstract: Tenodesis of the long head of the biceps tendon (LHB) at the upper part of the bicipital groove has been related to persistent postoperative bicipital pain. This is possibly due to the inflammation of the remaining tendon within the groove. This, in turn, could be attributed to the continual mechanical stress placed on the tendon in the narrow bicipital groove. Theoretically, should the LHB be more "relaxed," the mechanical stress applied on it would be diminished. On the basis of this rationale, we present an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
(12 reference statements)
1
12
0
3
Order By: Relevance
“…For this reason, many advocate a more distal tenodesis, suprapectoral or even subpectoral. 7 , 13 , 18 , 27 , 28 , 30 , 37 , 51 , 56 , 61 Nevertheless, we agree with Denard et al, 8 who has shown that a better LHB tendon length-tension relation recovery can be obtained with an interference screw adjacent to the articular margin of the humerus in a 25-mm-deep hole. Maybe the persistence of pathologic tendon tissue in the bicipital groove and not the tension increase per se is what precipitates pain on palpation.…”
Section: Discussionsupporting
confidence: 90%
“…For this reason, many advocate a more distal tenodesis, suprapectoral or even subpectoral. 7 , 13 , 18 , 27 , 28 , 30 , 37 , 51 , 56 , 61 Nevertheless, we agree with Denard et al, 8 who has shown that a better LHB tendon length-tension relation recovery can be obtained with an interference screw adjacent to the articular margin of the humerus in a 25-mm-deep hole. Maybe the persistence of pathologic tendon tissue in the bicipital groove and not the tension increase per se is what precipitates pain on palpation.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have mentioned the EBG [17,[25][26][27][28][29][30][31], but they did not de ne the EBG by rule and line. Many studies on tenodesis of the LBT valued a location 10 mm distal to the proximal EBG that anatomically lies superior to the pectoralis major tendon [25,26,30].…”
Section: Discussionmentioning
confidence: 99%
“…They found that this technique limited the risk of persistent tendon pathology and pain without a cosmetic deformity such as a Popeye sign. 15 This article presents a novel method in minimally invasive all-arthroscopic tenodesis by securing the proximal biceps tendon to the interference screw prior to fixation into the humerus. The benefits of the technique may avoid the tendon pullout from the screw-bone interface as described by Slabaugh et al 26 Although many techniques are used in practice and reported in the literature, it is certain that many young active patients with significant pathology will benefit from tenodesis.…”
Section: Discussionmentioning
confidence: 99%
“…They found that this technique limited the risk of persistent tendon pathology and pain without a cosmetic deformity such as a Popeye sign. 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation